Hacking Raspberry Pi - Warner, Timothy L. (Que, 2013)
DIY hardware hacking...easy as Pi ®! Raspberry Pi is taking off like a rocket! You can use this amazing, dirt-cheap, credit card-sized computer to learn powerful hardware hacking techniques as you build incredibly creative and useful projects! This complete, full-color guide requires absolutely no experience with either hardware hacking or computer programming. Colorful photos guide you through each project, and the step-by-step instructions are stunningly clear and easy! 1. Start with the absolute basics: Discover why millions of people are so passionate about the Pi! Tour the hardware, including storage, connections, and networking Install and run Raspbian, Raspberry Pi's Linux-based operating system Manage devices and configuration files Network Raspberry Pi and add Wi-Fi Program Raspberry Pi using Python, Scratch, XHTML, PHP, and MySQL 2. Next, build all these great projects: Media Center Retro Console Video Game Station Minecraft Server Web Server Portable Webcam Security & Privacy Device 3. Then, master all these cutting-edge techniques: Overclock Raspberry Pi for better performance Link Raspberry Pi to the Arduino and Arduino clones, including the AlaMode and the Gertboard Use the Pi to build electronics prototypes using a breadboard.